(untitled) (Research, Society and Development, 2021)
Maintaining hygienic conditions during production is considered a key part in obtaining innocuous food. Meat products can be contaminated by microorganisms during handling and processing. After being contaminated, the meat offers conditions for microorganisms to multiply, becoming a potential to convey pathogenic bacteria and a threat to consumer health. The application of self-control programs such as good manufacturing practices, standard operating hygiene procedure and hazard analysis and critical control points are implemented to ensure the safety and quality of products. Therefore, it is relevant to evaluate the hygienic and sanitary conditions of the establishments through the use of the checklist and sample collection through the swab, and through the samples is performed the identification of indicator microorganisms such as aerobic mesophiles, enterobacteria and total coliforms, which will reflect the hygienic and sanitary conditions of the site and product.